Silver mesostructures and core/shell structures (Au/AgNRs) for anti-bacterial effect - Hue, Do Thi (Vietnam Journal of Science and Technology, 2024)
A systematic and detailed study of the antibacterial efficacy of silver nanoparticles (AgNPs) with different structures synthesized by chemical methods is presented here. Silver mesostructures are synthesized in the presence of the weak reducing agent L-ascorbic acid (L-AA). Meatball-like unbranched mesostructures and coral-like branched nanostructures are obtained by adjusting precursor concentration AgNO3. The core/shell structures (Au/AgNRs) with controlled shells are prepared according to the seed growth method using gold nanorods (AuRs) as the hard template. The influence of silver nanoparticle‘s structure on antibacterial activity is investigated with different concentrations of silver nanoparticles on two types of bacteria: P.aeruginosa and S. aureus resistant while a positive control is Ampicillin 50 mg/ml. The results show that all samples had antibacterial properties comparable to or superior to those of Ampicillin. The concentration of particles is 50 µg/ml, the antibacterial performance is the highest. The more branched structure, and the higher the antibacterial ability.